Coordinate Systems, Numerical Objects and Algorithmic Operations of Computational Experiment in Fluid Mechanics (Global Journal of Science Frontier Research, 2016)
The paper deals with the computer implementation of direct computational experiments in fluid mechanics constructed on the basis of the approach developed bythe authors The proposed approach allows the use of explicit numerical scheme whichis an important condition for increasing the efficiency of the algorithms developed by numerical procedures with natural parallelism The paper examines the main objectsand operations that let you manage computational experiments and monitor the statusof the computation process Special attention is given to a realization of tensor representationsof numerical schemes for direct simulation b realization of representation of large particles of a continuous medium motion in two coordinate systems global andmobile c computing operations in the projections of coordinate systems direct and inversetransformation in these systems Particular attention is paid to the use of hardware and software of modern computer systems
Keywords: computer implementation; algorithms developed; fluid mechanics